(untitled) (Research, Society and Development, 2021)
The contemporary school has suffered a great impact due to the transformations that have taken place in society, being impelled to seek new teaching proposals in order to overcome school failure. Thus, in an attempt to give meaning to biology learning and make it more effective, more and more has been invested in the use of non-formal public spaces, in order to take advantage of the curiosity and availability of students so that the consolidation of the teaching process can occur. -learning, combining theory and practice. Thus, this work aimed to highlight the observation of birds in the Lagoa da Garça Park in Juína-MT, as a valid tool for teaching biology. For that, a didactic sequence was elaborated involving the accomplishment of an interpretative path, where students could be protagonists of the teaching-learning process. Before and after the execution of the didactic planning, the students answered questionnaires, called pre-test and post-test, which helped in verifying the validity of the didactic method used. Through the students’ answers, it can be seen that the proposed activity allowed them to know more about the local bird species, noting the ecological importance of these animals and the close relationship of the diversity of this group with the conservation status of the environment in which they live, providing opportunities for reflections on human attitudes that directly impact these beings.